Reflections on the ethics of participatory visual methods to engage communities in global health research. Issue 1 (1st January 2018) - Black, Gillian F.; Davies, Alun; Iskander, Dalia; Chambers, Mary
ABSTRACT: There is a growing body of literature describing conceptual frameworks for working with participatory visual methods (PVM). Through a global health lens, this paper examines some key themes within these frameworks. We reflect on our experiences of working with with an array of PVM to engage community members in Vietnam, Kenya, the Philippines and South Africa in biomedical research and public health. The participants that we have engaged in these processes live in under-resourced areas with high prevalence of communicable and non-communicable diseases. Our paper describes some of the challenges that we have encountered while using PVM to foster knowledge exchange, build relationships and facilitate change among individuals and families, community members, health workers, biomedical scientists and researchers. We consider multiple ethical situations that have arisen through our work and discuss the ways in which we have navigated and negotiated them. We offer our reflections and learning from facilitating these processes and in doing so we add novel contributions to ethical framework concepts.